Effect of Micronised Pumice Powder Addition on Shore-D Hardness Values of Medium Density Fiber Epoxy Composite - Ulay, Göksel; Koyuncu, Menderes (The Indonesian Institute of Science and Technology Research, 2024)
The present study explores the effect of MDF powder-reinforced filled pumice powder epoxy composites on their Shore - D properties, produced by using different weight percentage. The composites samples containing 10, 20, 30, 40, and 50wt% of pumice powder were fabricated by using hand lay-up technique. The specimens prepared were tested for hardness as per the ASTMD2240 standards. The outcomes of the study revealed that pumice powder amount in the composite increasing with an increased in Shore-D hardness values. It is noted that the weight percentage of 50% of pumice powder and 50% of MDF powder composite was produce the maximum hardness values.